2020
DOI: 10.20944/preprints202006.0261.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unbiased Approach for the Identification of Molecular Mechanisms Sensitive to Chemical Exposures

Abstract: Background: Targeted methods that dominated toxicological research until recently did not allow for screening of all molecular changes involved in toxic response. Therefore, it is difficult to infer if all major mechanisms of toxicity have already been discovered, or if some of them are still overlooked. Objectives: To identify molecular mechanisms sensitive to chemical exposures in an unbiased manner. Methods: We used data on 641,516 unique chemical-gene interactions from the Comparative Toxicogenomic Databas… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Additionally, the direction of change in gene expression was not considered when sensitivities of genes to chemical exposures were calculated. In fact, our previous study demonstrated that the absolute majority of highly chemically-sensitive genes are induced and suppressed by almost equal number of compounds [15]. Similarly, high level of generalization does not allow accounting for individual differences in patients' response to COVID-19, including differences determined by age, sex, race, comorbidities, and other factors.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Additionally, the direction of change in gene expression was not considered when sensitivities of genes to chemical exposures were calculated. In fact, our previous study demonstrated that the absolute majority of highly chemically-sensitive genes are induced and suppressed by almost equal number of compounds [15]. Similarly, high level of generalization does not allow accounting for individual differences in patients' response to COVID-19, including differences determined by age, sex, race, comorbidities, and other factors.…”
Section: Discussionmentioning
confidence: 91%
“…According to our hypothesis, speci c immune response mechanisms may be synergistically affected by chemical exposures and SARS-CoV-2, resulting in increased severity of the disease. To test this hypothesis, we rst used data on the sensitivity of mammalian genes to chemical exposures identi ed in our previous research [15,17] by overlaying transcriptomic datasets from many individual toxicological genomic studies. This allowed the identi cation of genes that respond most often to a variety of chemical exposures (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations